Nurses' Knowledge of Nonalcoholic Fatty Liver Disease: A Cross-sectional Study: Pengetahuan Perawat tentang Penyakit Hati Berlemak Nonalkohol: Sebuah Studi Cross-sectional - Eman H. Rahi; Zahraa Mahmoud Hussain Al-Hejaj; Ali Malik Tiryag (Academia Open, 2024)
General Background: Non-alcoholic fatty liver disease (NAFLD) encompasses a spectrum of liver conditions, including simple steatosis, cirrhosis, liver cancer, and non-alcoholic steatohepatitis (NASH). Specific Background: Given the increasing prevalence of NAFLD, understanding healthcare professionals' knowledge about this condition is crucial for effective patient care and management. Knowledge Gap: However, there is limited research assessing nurses' knowledge regarding NAFLD, particularly in the context of Basrah City Center Hospitals. Aims: This study aimed to evaluate nurses' knowledge of NAFLD and investigate its relationship with demographic characteristics such as gender, age, years of experience, and departmental affiliation. Results: A cross-sectional survey involving 150 nurses revealed that 57.3% possessed high levels of knowledge regarding NAFLD, while 34% had moderate knowledge. Notably, a significant correlation was found between nurses working at Al-Shifaa Hospital and their knowledge levels. The majority of participants were female (64.7%) and aged 20-30 (72%), with a predominant educational background from Nursing Institutes (39.3%) and fewer than five years of experience (56%). Novelty: This study is pioneering in assessing the knowledge of NAFLD among nurses in Basrah, highlighting specific areas of strength and weakness in their understanding. Implications: The study highlights the need for targeted educational interventions to improve nurses' understanding of NAFLD, leading to improved patient care and outcomes in liver disease management. practice. Highlights: Increasing NAFLD prevalence necessitates enhanced healthcare provider awareness. Nurses showed significant knowledge levels about NAFLD. Knowledge varies significantly by hospital affiliation. Keywords: Non-alcoholic fatty liver disease, nurses' knowledge, Basrah City, cross-sectional study, healthcare education.